Analisis Value Chain Sebagai Alat Strategic Cost Management untuk Menciptakan Keunggulan Bersaing dalam Upaya Meningkatkan Profitabilitas Perusahaan (Studi pada Unit Bisnis Air Minum Dalam Kemasan (AMDK) ASA Perum Jasa Tirta 1 Malang) - Ema Maliawati; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2023)
The purpose of this study was to analyze the value chain analysis as a tool of strategic cost management to create a competitive advantage in an effort to improve the profitability of the company with the object of research on Bottled Drinking Water (bottled water) ASA Perum Jasa Tirta 1 Malang. With the application of value chain analysis used can be seen activity which can be decisive in a competitive advantage. The results obtained from the analysis of the value chain where inbound logistics activity of 27,48% of the total cost of the primary activities and human resource management for 20,72% of the total cost of secondary activity. And both have the largest proportion in each activity. And for activities smallest proportion of the cost is the activity of service that is 1,38% of the total primary activity and procurement activities, namely 0,65% of the total secondary activity. The objectives to be achieved in the application of value chain analysis is about to that there is a link between the activities of primary and secondary activities. This association appears in terms of coordination and optimization between activities that can support companies in proving competitive advantage and profitability.Keywords: Value chain analysis, strategic management, competitive advantage, competitive strategy, activities value, cost leadership.